2014
DOI: 10.1128/iai.00862-13
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NLRP3 and AIM2 Inflammasomes by Porphyromonas gingivalis Infection

Abstract: Porphyromonas gingivalis, a major periodontopathogen, is involved in the pathogenesis of periodontitis. Interleukin-1␤ (IL-1␤), a proinflammatory cytokine, regulates innate immune responses and is critical for the host defense against bacterial infection. However, excessive IL-1␤ is linked to periodontal destruction. IL-1␤ synthesis, maturation, and secretion are tightly regulated by Toll-like receptor (TLR) signaling and inflammasome activation. We found much higher levels of inflammasome components in the gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
198
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(222 citation statements)
references
References 39 publications
17
198
0
3
Order By: Relevance
“…2). In fact, among all the genes, IL-1β was the only one that was examined and found to be involved in periodontal tissue destruction in GCF in a previous study (28). In addition, the expression levels of ASC and CASP1 were significantly upregulated in the GCF of patients with gingivitis compared with healthy controls in the present study (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…2). In fact, among all the genes, IL-1β was the only one that was examined and found to be involved in periodontal tissue destruction in GCF in a previous study (28). In addition, the expression levels of ASC and CASP1 were significantly upregulated in the GCF of patients with gingivitis compared with healthy controls in the present study (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Our current study demonstrates that P. gingivalis fimbriae are able to inhibit IL-1β at the second signal level by interfering with ATP signaling through the purinergic receptor, P2X7. A recent work [46] reported that P. gingivalis activates ATP release and that the inhibition of K + efflux by increasing extracellular K + concentration blocked caspase-1 activation, IL-1β secretion, and pyroptic cell death induced by this pathogen. Here, we showed that this mechanism of IL-1β secretion by P. gingivalis is not only dependent of K + efflux but it also involves the participation of iPLA 2 which is related to fusion of secretory lysosomes with the plasma membrane in the non-classical secretory events induced by eATP stimulation [25].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest a key role for this receptor in the elimination process. Previous studies have shown the ability of infecting pathogens to cause ATP release in a physiological form (22,23). Thus, we measured the ATP release during infection with L. amazonensis at different time points.…”
Section: P2x7 Receptor Is Involved In L Amazonensis Elimination Medimentioning
confidence: 99%